1977
DOI: 10.1007/bf00273261
|View full text |Cite
|
Sign up to set email alerts
|

?-Galactosidase deficiency in juvenile and adult patients

Abstract: Six juvenile and adult patients with progressive neurological diseases and beta-galactosidase deficiency were reported. Any diseases known to date were denied. These cases together with ten case reports in the literature were reviewed and were classified into three groups from clinical and biochemical points. Group 1 patients were characterized by progressive ataxia and myoclonus with gargoyl changes and macular cherry-red spots. In this syndrome beta-galactosidase activity seems to be secondarily affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…The primary molecular defect in GM1 gangliosidosis and Morquio B syndrome is a deficiency of this enzyme. On the other hand, a hereditary disorder with i-galactosidase deficiency showing different clinical phenotypes from GM1 gangliosidosis was reported by Suzuki et al [71] and subsequently found to be a new lysosomal storage disease on the basis of clinical and biochemical analyses by Wenger et al [72]. The patients showed enzyme deficiency of neuraminidase as well as i-galactosidase, suggesting this genetic variant was different from other i-galactosidase deficiency diseases.…”
Section: Cathepsin a As An Essential Constituent Of The Lysosomal -Gamentioning
confidence: 93%
“…The primary molecular defect in GM1 gangliosidosis and Morquio B syndrome is a deficiency of this enzyme. On the other hand, a hereditary disorder with i-galactosidase deficiency showing different clinical phenotypes from GM1 gangliosidosis was reported by Suzuki et al [71] and subsequently found to be a new lysosomal storage disease on the basis of clinical and biochemical analyses by Wenger et al [72]. The patients showed enzyme deficiency of neuraminidase as well as i-galactosidase, suggesting this genetic variant was different from other i-galactosidase deficiency diseases.…”
Section: Cathepsin a As An Essential Constituent Of The Lysosomal -Gamentioning
confidence: 93%
“…Age of onset is quite variable but usually is during the late infantile or juvenile period and survival is to adulthood. Clinically this type is character ized by pyramidal and extrapyramidal signs with gait disturbance and dystonic movements (table 1) [10][11][12][13][14][15]. Cases studied postmortem were limited to 3 but all showed similar unique distributional patterns of neu ronal storage affecting primarily basal ganglia [12,13].…”
Section: Gm] Gangliosidosismentioning
confidence: 99%
“…Since the observation by Okada and O'Brien (3) that the autosomal recessive disease Gm1-gangliosidosis is due to a /3-galactosidase deficiency, various patients with infantile, juvenile, and adult forms of this disease have been reported (4)(5)(6)(7). Analyses of interspecies hybrids indicated that the ,B-galactosidase deficiency in the various forms ofGM1-gangliosidosis is based on a mutation of a structural gene on chromosome 3 coding for the enzyme polypeptide (8).…”
mentioning
confidence: 99%